Capacitor Bank Panel Design to Improve Industrial Power System Efficiency and Safety: Rancangan Panel Kapasitor Bank untuk Meningkatkan Efisiensi dan Keamanan Sistem Daya Industri - Adhimanata, Yogi; A, Shazana Dhiya (Universitas Muhammadiyah Sidoarjo, 2024)
Industrial loads generally use control equipment and power electronics that use semiconductor materials that are very sensitive to voltage fluctuations. As reactive power compensation, industries usually use capacitor banks to increase power factor, reduce losses and increase line capacity. But it turns out that the use of capacitor banks also causes problems related to capacitor bank switching during the energizing process. During the energizing process, transient voltages and currents will be generated which can potentially damage control equipment, power electronic equipment, switching equipment and the capacitor bank itself. The Capacitor Bank panel assembly process involves the preparation of components such as MCB (Miniature Circuit Breaker), MCCB (Molded Case Circuit Breaker), Capacitor Bank, and other components. After that, these components are carefully assembled according to the pre-prepared design. Next, the installation of the Capacitor Bank panel involves mounting the panel to the location according to the plan and connecting it to the building's main power system. Accurate wiring and meticulous testing are required to ensure that the panels function properly. Therefore, a good understanding of the assembly and installation process of Capacitor Bank panels is essential to ensure efficient, and safety.